การประเมินความเสี่ยงของการปลูกข้าวโพดเลี้ยงสัตว์ในภาคเหนือของประเทศไทย - รุ่งทิวา สุยะ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The present investigation aims to gain an insight into (1) the risk functions of average product price and production cost of maize production, (2) the economic return to farmers and the probability of their getting profit or loss from maize production, and (3) the risk factors having effects on profit. It is based on secondary data related to maize production in six districts located in four provinces in the North of Thailand. Specifically, data were compiled from various research papers, statistics and annual reports of pertinent government agencies covering the annual data on production cost of maize, average output, and wage rate during 2003 – 2013; and monthly data on maize price, prices of 15-15-15, 16-20-0, and 40-0-0 fertilizers, and retailed diesel price during the same period. For the analysis, BestFit software program was used to derive the distribution functions of data or the risk functions of various random variables. Furthermore, @Risk software program was applied for risk assessment of the loss from maize production in each province under different scenarios. Curve fitting by Bestfit program revealed distribution functions of risk factors vary across different maize production areas. The distribution functions of the first season maize output data took three forms: Log-Logistic, Inverse Gaussian and Logistic; while those of the second season maize production were of Extreme Value and Normal types. Prices of the first season maize were found to distribute as Normal, Weibull and Logistic functions while prices of the second season maize distribute as Pearson Type 3, Triangular, and Inverse Gaussian functions. Distribution function of 15-15-15 fertilizer price is in the form of Normal while that of 16-20-0 formula is of Triangular pattern. Price data of 46-0-0 fertilizer, however, distribute as both Triangular and Uniform functions. Distribution function of wage rate also takes two forms, Extreme Value and Log-logistic. Meanwhile, the diesel price series distribute as Beta General function. The analysis on revenue above cash cost revealed that maize growers in all districts under study got profit from the first season maize production. The highest profit was realized by those in LomSak District of Phetchabun Province at 2,866 baht per rai on average, while the lowest profit occurred in Mae Chaem District of Chiang Mai Province at averagely 1,346 baht per rai. The second season maize production was far more profitable compared to the first season for farmers in all districts. However, the highest profit from the second maize cropping was received in NongPhai District of Phetchabun Province at 3,675 baht per rai on the average and the lowest in Na Noi District of Nan Province at averagely 3,033 baht per rai. The risk assessment on the basis of revenue above cash cost provided the results that in the first season maize production, maize growers in Mae Chaem have the greatest chance or 16 % to get financial loss while those in Theong District of Chiang Rai Province face the smallest chance or 2 % to face this problem. On the basis of net profit, production of the first season maize has greater chance to encounter loss. For the second season maize production, the risk assessment on the basis of revenue above cash cost indicated that virtually all maize growers under study have no chance or 0 % to get loss, except those in Mae Chaem District for which the analysis could not be made due to inadequate data. On the basis of net profit, the risk assessment provided a result that maize growers in all districts under investigation have the likelihood to face relatively smaller extent of loss from the second season maize production compared to the first season. Those second season maize growers in NongPhai District of Phetchabun Province are expected to get the least chance or less than 2 % to face loss. Meanwhile, maize growers in Thoeng District of Chiang Rai Province and Lom Kao District of Phetchabun Province are likely to face greater chance of loss from the second cropping compared to the first, the increase from 10 % to 12 % and 6 % to 7 % respectively. The sensitivity analysis, taking into account only cash cost, suggested that the increase or decrease in output price and in maize yield are the most important risk factors for maize growers in all areas under study and in both maize growing seasons. The results from this investigation lead to the policy implications that the lowering of risk from financial loss of maize growers can be made possible by research and market measures. Specifically, research programs should be arranged with focus on breeding pest and disease resistant maize varieties or farm management techniques for minimizing or controlling pests and diseases so as to improve maize yield. Some other policies should also be designed to enable maize growers to obtain higher farm prices.